(untitled) (Research, Society and Development, 2021)
In Brazil up to 80% of companies are unable to maintain themselves, so they close in the first year of operation. Often, this problem is due to a lack of preparation of entrepreneurs. Among the main causes, we can mention some that could be avoided, such as: lack of market research, lack of planning, lack of marketing and management techniques, lack of knowledge of the target audience, among others. This paper reports an extension project developed at the Federal Institute of Mato Grosso that identified and selected micro and small entrepreneurs who had their businesses in a vulnerable zone (at risk of closing) or informal entrepreneurs with the potential to formalize and grow. In this project, training in entrepreneurial administration was provided to these entrepreneurs, through an Initial Formation (IF) course, and guidance and mentoring during and immediately after completion of the course, so that they can manage their businesses with the knowledge learned. The training and guidance and mentoring helped them to work in the diagnosis and solution of their vulnerabilities.